Proceedings of the First International Workshop on Issues of Sentiment Discovery and Opinion Mining 2012
DOI: 10.1145/2346676.2346686
|View full text |Cite
|
Sign up to set email alerts
|

Fast learning for sentiment analysis on bullying

Abstract: Bullying is a serious national health issue among adolescents. Social media offers a new opportunity to study bullying in both physical and cyber worlds. Sentiment analysis has the potential to identify victims who pose high risk to themselves or others, and to enhance the scientific understanding of bullying overall. We identify seven emotions common in bullying. While some of the emotions are well-studied before, others are non-standard in the sentiment analysis literature. We propose a fast training procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…On an individual basis: anger, negative feelings and feelings of inferiority, feeling demotivated, feelings of fear and intimidation, feeling emotional and upset, irritation, loss of self-esteem, stress and wasted time. These findings are in line with previous research (Xu & Zhu, 2012;Lam & Li, 2013);…”
Section: Effects Of Cyber Incivilitysupporting
confidence: 94%
See 1 more Smart Citation
“…On an individual basis: anger, negative feelings and feelings of inferiority, feeling demotivated, feelings of fear and intimidation, feeling emotional and upset, irritation, loss of self-esteem, stress and wasted time. These findings are in line with previous research (Xu & Zhu, 2012;Lam & Li, 2013);…”
Section: Effects Of Cyber Incivilitysupporting
confidence: 94%
“…Emotions that are associated with cyberbullying victims are anger, embarrassment, empathy, fear, pride, relief (when the situation is resolved) and sadness (Xu & Zhu, 2012). Victims also display bad moods (Tokunaga, 2010).…”
Section: Effects and Impactmentioning
confidence: 99%
“…Dadvar et al [10] detected cyberbullies instead of detecting text content; Nahar et al [21] used social networks to present a graph model, identifying the most active cyberbullying predators and victims; Xu et al [31] explored the detection of roles within cyberbullying, and identified those of bully, victim, accuser and reporter. In addition, research [30,13,29] used Latent Dirichlet Allocation (LDA) to extract the main topics for each text content.…”
Section: Related Workmentioning
confidence: 99%
“…Their tasks consisted of obtaining traces via the twitter streaming API to find an instance of the word "bully" in tweets and build an eight classes text classifier based on pre-defined emotion classes [15]. Henri et al (2012) showed that it is possible to predict real-world threats by extracting abnormalities in tweets [16].…”
Section: Xu Et Al (2012) Have Detected Traces Of Bullying On Thementioning
confidence: 99%